Nutritional Ecology of the Ruminant - Van Soest, Peter J. (Book collections on Project MUSE., 1994)
This monumental text-reference places in clear persepctive the importance of nutritional assessments to the ecology and biology of ruminants and other nonruminant herbivorous mammals. Now extensively revised and significantly expanded, it reflects the changes and growth in ruminant nutrition and related ecology since 1982.Among the subjects Peter J. Van Soest covers are nutritional constraints, mineral nutrition, rumen fermentation, microbial ecology, utilization of fibrous carbohydrates, application of ruminant precepts to fermentive digestion in nonruminants, as well as taxonomy, evolution, nonruminant competitors, gastrointestinal anatomies, feeding behavior, and problems fo animal size. He also discusses methods of evaluation, nutritive value, physical struture and chemical composition of feeds, forages, and broses, the effects of lignification, and ecology of plant self-protection, in addition to metabolism of energy, protein, lipids, control of feed intake, mathematical models of animal function, digestive flow, and net energy.Van Soest has introduced a number of changes in this edition, including new illustrations and tables. He places nutritional studies in historical context to show not only the effectiveness of nutritional approaches but also why nutrition is of fundamental importance to issues of world conservation. He has extended precepts of ruminant nutritional ecology to such distant adaptations as the giant panda and streamlined conceptual issues in a clearer logical progression, with emphasis on mechanistic causal interrelationships.Peter J. Van Soest is Professor of Animal Nutrition in the Department of Animal Science and the Division of Nutritional Sciences at the New York State College of Agriculture and Life Sciences, Cornell University.